The Effect of Mathematics Learning Approaches and Self-Regulation to Recognize the Concept of Early Numbers Ability - Jhoni Warmansyah; Restu Yuningsih; Evi Selva Nirwana; Ravidah; Rahmanda Putri; Amalina; Masril (Program Studi Magister Pendidikan Anak Usia Dini, 2023)
The ability to recognize the concept of early numbers in early childhood is very important to develop so that children are ready to take part in learning mathematics at a higher level. This study aims to determine the effect of mathematics learning approaches and self-regulation to recognize the concept of early numbers ability in kindergarten. The study used an experimental method with a treatment design by level 2x2. The sample used was 32 children. Score data, ability to recognize number concepts, analyzed and interpreted. The results showed that: (1) The Realistic Mathematics Education approach is better than the Open Ended Approach in improving the ability to recognize children's number concepts; (2) There is an interaction effect between mathematics learning approaches and Self-Regulation to recognize the concept of early numbers ability; (3) The Realistic Mathematics Education approach is more suitable for children with high self-regulation, (4) The Open Ended approach is more suitable for children with low self-regulation. Subsequent experiments are expected to find mathematics learning approaches for children whose self-regulation is low on recognizing the concept of early numbers ability. Keywords: mathematics learning approach, self-regulation, early number concept ability References: Adjie, N., Putri, S. U., & Dewi, F. (2019). Penerapan Pendidikan Matematika Realistik (PMR) dalam Meningkatkan Pemahaman Konsep Bilangan Cacah pada Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 4(1), 336. https://doi.org/10.31004/obsesi.v4i1.338 Adjie, N., Putri, S. U., & Dewi, F. (2020). Peningkatan Kemampuan Koneksi Matematika melalui Pendidikan Matematika Realistik (PMR) pada Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(2), 1325–1338. https://doi.org/10.31004/obsesi.v5i2.846 Adjie, N., Putri, S. U., & Dewi, F. (2021). Improvement of Basic Math Skills Through Realistic Mathematics Education (RME) in Early Childhood. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(3), 1647–1657. https://doi.org/10.31004/obsesi.v6i3.1832 Amalina, A. (2020). Pembelajaran Matematika Anak Usia Dini di Masa Pandemi COVID-19 Tahun 2020. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 538. https://doi.org/10.31004/obsesi.v5i1.592 Amalina, A., Yanti, F., & Warmansyah, J. (2022). Penerapan Pendekatan Matematika Realistik terhadap Kemampuan Pemahaman Konsep Pengukuran pada Anak Usia 5-6 Tahun. Aulad: Journal on Early Childhood, 5(2), 306–312. https://doi.org/10.31004/aulad.v5i2.378 Amini, F., Munir, S., & Lasari, Y. L. (2022). Student Mathematical Problem Solving Ability in Elementary School: The Effect of Guided Discovery Learning. Journal of Islamic Education Students (JIES), 2(2), 49. https://doi.org/10.31958/jies.v2i2.5592 Anselmus, Z., & Parikaes, P. (2018). Regulasi Diri Dalam Belajar Sebagai Konsekuen. Jurnal Penelitain Dan Pengembangan Pendidikan, 1(1), 82–95. Apriani, N., & Maryam, K. (2020). Pengaruh Pendekatan Realistic Matematick Edukation (RME) Terhadap Kemampuan Pemecahan Masalah. 3(1), 12–19. Ardiniawan, D. Y., Subiyantoro, S., & Kurniawan, S. B. (2022). Peningkatan Kemampuan Penalaran Matematis Siswa Sekolah Dasar Melalui Pendekatan Realistic Mathematics Education ( RME ) Siswa SD Se-Kecamatan Pacitan. April, 607–613. Asri Devi, N. M. I. (2020). Pengembangan Media Pembelajaran Puzzle Angka untuk Meningkatkan Kemampuan Mengenal Lambang Bilangan. Jurnal Ilmiah Pendidikan Profesi Guru, 3(3), 416. https://doi.org/10.23887/jippg.v3i3.28331 Aulia, M., & Amra, A. (2021). Parent’s Participation in Improving the Quality of Education in Elementary Schools. Journal of Islamic Education Students (JIES), 1(2), 58. https://doi.org/10.31958/jies.v1i2.3004 Aziza, A., Pratiwi, H., & Ageng Pramesty Koernarso, D. (2020). Pengaruh Metode Montessori dalam Meningkatkan Pemahaman Konsep Matematika Anak Usia Dini di Banjarmasin. AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 6(1), 15–26. https://doi.org/10.14421/al-athfal.2020.61-02 Becker, D. R., Miao, A., Duncan, R., & Mcclelland, M. (2014). Behavioral self-regulation and executive function both predict visuomotor skills and early academic achievement. Early Childhood Research Quarterly, 1–14. https://doi.org/10.1016/j.ecresq.2014.04.014 Bohlmann, N. L., & Downer, J. T. (2016). Self-Regulation and Task Engagement as Predictors of Emergent Language and Literacy Skills. Early Education and Development, 27(1), 18–37. https://doi.org/10.1080/10409289.2015.1046784 Brandes-Aitken, A., Braren, S., Swingler, M., Voegtline, K., & Blair, C. (2019). Sustained attention in infancy: A foundation for the development of multiple aspects of self-regulation for children in poverty. Journal of Experimental Child Psychology, 184, 192–209. https://doi.org/10.1016/j.jecp.2019.04.006 Charlesworth, R. (2005). Experiences in Math for Young Children Fifth Edition (3rd edition). Delmar Cengage Learning. Charlesworth, R. (2011). Understanding child development. Wadsworth Publishing. Chisara, C., Hakim, D. L., & Kartika, H. (2018). Implementasi Pendekatan Realistic Mathematics Education (RME) Dalam Pembelajaran Matematika. Prosiding Sesiomadika, 65–72. Cobb, P., Zhao, Q., & Visnovska, J. (2008). Learning from and adapting the theory of realistic mathematics education. Éducation et Didactique, 2(1), 105–124. Coelho, V., Cadima, J., Pinto, A. I., & Guimarães, C. (2019). Self-Regulation, Engagement, and Developmental Functioning in Preschool-Aged Children. Journal of Early Intervention, 41(2), 105–124. https://doi.org/10.1177/1053815118810238 Cohen−Swerdlik. (2009). Psychology: Psychological Testing and Assessment An Introduction to Test and Measurement 7th Edition. In McGraw-Hill (7th ed.). McGraw-Hill. https://doi.org/13: 9780767421577 Costa, P., Ermini, T., & Sigaud, C. H. de S. (2019). Effects of an educational playful intervention on nasal hygiene behaviors of preschoolers: a quasi-experimental study. Health Promotion Perspectives, 9(1), 50–54. https://doi.org/10.15171/hpp.2019.06 Deflorio, L., Klein, A., Starkey, P., Swank, P. R., Taylor, H. B., Halliday, S. E., Beliakoff, A., & Mulcahy, C. (2018). A study of the developing relations between self-regulation and mathematical knowledge in the context of early math intervention. Early Childhood Research Quarterly. https://doi.org/10.1016/j.ecresq.2018.06.008 Delyana, H. (2015). Peningkatan Kemampuan Pemecahan Masalah Matematika Siswa Kelas VII Melalui Penerapan Pendekatan Open Ended. Lemma, 2(1), 26–34. Dennick, R. (2016). Constructivism: reflections on twenty-five years teaching the constructivist approach in medical education. International Journal of Medical Education, 7(July), 200–205. https://doi.org/10.5116/ijme.5763.de11 Deny, S. (2019). Survei PISA 2018: Skor Pendidikan Indonesia Masih di Bawah Rata-Rata. 04 Desember. Dwipayana, I. K. A. A., & Diputra, K. S. (2019). Pengaruh Pendekatan Pendidikan Matematika Realistik Berbasis Open Ended Terhadap Kemampuan Berpikir Kreatif Siswa. Journal of Education Technology, 2(3), 87. https://doi.org/10.23887/jet.v2i3.16380 Egbert, J., Herman, D., & Lee, H. (2015). Flipped Instruction in English Language Teacher Education : A Design- ‐ based Study in a Complex, Open- ‐ ended Learning Environment. 19(2), 1–23. Eisenberg, N., Pidada, S., & Liew, J. (2001). The Relations of Regulation and negative emotionality to Indonesian Children’s social functioning. Child Development, 72(6), 1747–1763. https://doi.org/10.1111/1467-8624.00376 Eisenberg, N., Valiente, C., & Eggum, N. D. (2010). Self-Regulation and School Readiness. Early Education & Development, 21(5), 681–698. https://doi.org/10.1080/10409289.2010.497451 Eka, F. (2016). Penerapan Model Pembelajaran Open Ended Pada Pembelajaran Matematika Kelas V Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa di Madrasah Ibtidaiyah Al-Munawwarah Kota Jambi. Skripsi, 4(1), 1–23. Elina, R. (2021). Journal of Islamic Education Students The Effect of Administrative Services on Students’ Satisfaction. JIES: Journal of Islamic Education Students, 1(1), 39–47. Elliott, W., Jung, H., & Friedline, T. (2016). Math Achievement and Children’s Savings: Implications for Child Development Accounts. Journal of Family and Economic Issues, 31(2), 171–184. https://doi.org/10.1007/s10834-010-9185-4 Evi, S. (2011). Pendekatan Matematika Realistik (PMR) untuk Meningkatkan Kemampuan Berfikir Siswa di Tingkat Sekolah Dasar. Jurnal Penelitian Pendidikan, Edisi Khus(2), 154–163. Fajriah, N., & Asiskawati, E. (2015). Kemampuan Berfikir Kreatif Siswa dalam Pembelajaran Matematika Menggunakan Pendidikan Matematika Realistik di SMP. Pendidikan Matematika, 3(2), 157–165. Faridah, N., Isrok’atun, I., & Aeni, A. N. (2016). Pendekatan Open-Ended Untuk Meningkatkan Kemampuan Berpikir Kreatif Matematis Dan Kepercayaan Diri Siswa. Jurnal Pena Ilmiah, 1(1). Fathonah, R. N. (2021). Video Kegiatan Rote Counting dan Rational Counting untuk Menstimulasi Berhitung Permulaan pada Anak Usia ( 4-5 ) Tahun. https://doi.org/10.36706/jtk.v8i2.14630 Febriyani, E., & Warmansyah, J. (2021). Akreditasi Satuan PAUD Berbasis Sistem Penilaian Akreditasi (SISPENA). Journal of Science and Technology, 1(2), 3. Friskilia, O., & Winata, H. (2018). Regulasi Diri (Pengaturan Diri) Sebagai Determinan Hasil Belajar Siswa Sekolah Menengah Kejuruan. Jurnal Pendidikan Manajemen Perkantoran, 3(1), 184. https://doi.org/10.17509/jpm.v3i1.9454 Frye, D., Baroody, A. J., Burchinal, M., Carver, S. M., Jordan, N. C., & McDowell, J. (2014). Teaching math to young children: A practice guide (NCEE 2014-4005). Department of Education. García-Sánchez, P., Tonda, A., Mora, A. M., Squillero, G., & Merelo, J. J. (2018). Automated playtesting in collectible card games using evolutionary algorithms: A case study in Hearthstone. Knowledge-Based Systems, 153, 133–146. https://doi.org/10.1016/j.knosys.2018.04.030 Greenberg, J. (2012). M ore, A ll G one , E mpty , Every Day in Every Way Coming soon ! May, 62–64. Hamidah, N. H., Lidinillah, D. A. M., & Muslihin, H. Y. (2021). Desain Lembar Kerja Anak Berbasis Realistic Mathematika Education ( RME ) untuk Mengenalkan Konsep Bilangan Anak Usia Sciencs Study ) siswa Negara Indonesia. 5(1), 1–9. Handayani, S. D., & Irawan, A. (2020). Pembelajaran matematika di masa pandemic covid-19 berdasarkan pendekatan matematika realistik. Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah Di Bidang Pendidikan Matematika, 6(2), 179–189. https://doi.org/10.29407/jmen.v6i2.14813 Haryuni, S. (2013). Peningkatan Kemampuan Mengenal Bilangan Melalui Media Domino Segitiga di PAUD Kenanga I Kabupaten Pesisir Selatan. Spektrum PLS, 1(1), 103–118. Hayati, N., & Fitri, R. (2016). Bombik Modifikasi Pada Anak Kelompok Bermain. Jurnal Paud Teratai, 5(3), 1–5. Hendrik, J., & Susanti. (2019). Perancangan Aplikasi Tes Psikologi Kecerdasan Majemuk Menggunakan Howard Gardner ’ S Theory of Multiple Intelligences Dengan Microsoft Visual Basic . Net. Jurnal TIMES, VIII(1), 54–62. Hidayat, E. I. F., Vivi Yandhari, I. A., & Alamsyah, T. P. (2020). Efektivitas Pendekatan Realistic Mathematics Education (RME) Untuk Meningkatkan Kemampuan Pemahaman Konsep Matematika Siswa Kelas V. Jurnal Ilmiah Sekolah Dasar, 4(1), 106. https://doi.org/10.23887/jisd.v4i1.21103 Hurtado, C. M. (2017). The Role Of And Quality Of Head Start Experiences In the Development Of Self-Regulatation. Ivrendi, A. (2011). Influence of Self-Regulation on the Development of Children’s Number Sense. Early Childhood Education Journal. https://doi.org/10.1007/s10643-011-0462-0 Jampel, I. N., & Puspita, K. R. (2017). Peningkatan Hasil Belajar Siswa Sekolah Dasar Melalui Aktivitas Pembelajaran Mengamati Berbantuan Audiovisual. International Journal of Elementary Education, 1(3), 197. https://doi.org/10.23887/ijee.v1i3.10156 Jaramillo, J. M., Rendón, M. I., Muñoz, L., Weis, M., Trommsdorff, G., & Medina, A. M. (2017). Children s Self-Regulation in Cultural Contexts : The Role of Parental Socialization Theories, Goals, and Practices. 8(June), 1–9.https://doi.org/10.3389/fpsyg.2017.00923 Jennifer, J. C., Margaret, M., & Leow, C. (2014). A Survey Study of Early Childhood Teachers ’ Beliefs and Confidence about Teaching Early Math. 367–377. https://doi.org/10.1007/s10643-013-0619-0 Kurnia. (2015). Penerapan Model Problem Based Learning Untuk Meningkatkan Kemampuan Menulis Teks Eksposisi Pada Siswa Kelas X II-4 SMA Negeri 8 Makassar. Jurnal Pepatudzu, 9(1), 72–84. Laela, M. N., Ashari, F. A., & Nurcahyani, L. D. (2023). Development of APE Jemari Keahlian to Develop Cognitive Abilities in Children 4-5 Years Old. Indonesian Journal of Early Childhood Educational Research, 1(2), 97–106. https://doi.org/10.31958/ijecer.v1i2.8158 Lau, Y. S., & Rahardjo, M. M. (2020). Meningkatkan Budaya Antri Anak Usia 4-5 Tahun melalui Metode Berbaris Sesuai Warna. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1), 755. https://doi.org/10.31004/obsesi.v5i1.624 Liwis, N. W. N., & Antara, P. A. (2017). Pengaruh Model Pembelajaran Matematika Realistik Terhadap Kemampuan Mengenal Konsep Bilangan Pada Anak Kelompok A Taman Kanak-Kanak Gugus V Kecamatan Buleleng Gugus V Kecamatan Buleleng Tahun Ajaran 2016/2017. Jurnal Pendidikan Anak Usia Dini Undiksha, 5(1). https://doi.org/http://dx.doi.org/10.23887/paud.v5i1.11403 Manab, A. (2016). Memahami regulasi diri: Sebuah tinjauan konseptual. Psychology & Humanity, 7–11. McGuire, P., Kinzie, M. B., & Berch, D. B. (2012). Developing Number Sense in Pre-K with Five-Frames. Early Childhood Education Journal. https://doi.org/10.1007/s10643-011-0479-4 Mclaughlin, T., Gordon, C., & Ayivor, J. (2013). An Evaluation of the Direct Instruction Model-Lead-Test Procedure and Rewards on Rote Counting, Number Recognition... Indonesian Journal of Basic and Applied Science, 2(1), 98–109. Mullis, I. V. S., Martin, M. O., Foy, P., & Hooper, M. (2015). TIMSS 2015 International Results in Mathematics. Mulyana, F. A. P., Nandiyanto, A. B. D., & Kurniawan, T. (2022). E-learning Media for the Ability to Recognize and Count Numbers in Kindergarten Students. International Journal of Research and Applied Technology, 2(1), 151–157. https://doi.org/10.34010/injuratech.v2i1.6784 Mulyati, C., Muiz, D. A., & Rahman, T. (2019). Pengembangan Media Papan Flanel Untuk Memfasilitasi Kemampuan Konsep Bilangan Anak Pada Kelompok B. Jurnal Pendidikan Dan Konseling (JPDK), 1(1), 59–68. https://doi.org/10.31004/jpdk.v1i1.362 Mulyati, S., & Sisrazeni, S. (2022). The Relationship Between Stressful Study And Students’ Sleep Pattern During Covid-19 Pandemic. Journal of Islamic Education Students (JIES), 2(1), 21. https://doi.org/10.31958/jies.v2i1.4384 Mustikasari, M., Zulkardi, Z., & Aisyah, N. (2013). Pengembangan Soal-Soal Open-Ended Pokok Bahasan Bilangan Pecahan Di Sekolah Menengah Pertama. Jurnal Pendidikan Matematika, 4(2). https://doi.org/10.22342/jpm.4.2.820 . Muzakki, M., & Fauziah, P. Y. (2015). Implementasi pembelajaran anak usia dini berbasis budaya lokal di PAUD full day school. Jurnal Pendidikan Dan Pemberdayaan Masyarakat, 2(1), 39. https://doi.org/10.21831/jppm.v2i1.4842 Nabighoh, W. N., Mustaji, M., & Hendratno, H. (2022). Meningkatkan Kecerdasan Logika Matematika Anak Usia Dini melalui Media Interaktif Puzzle Angka. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(4), 3410–3417. https://doi.org/10.31004/obsesi.v6i4.2410 Narayani, N. P. U. D. (2019). Pengaruh Pendekatan Matematika Realistik Berbasis Pemecahan Masalah Berbantuan Media Konkret Terhadap Hasil Belajar Matematika. Jurnal Ilmiah Sekolah Dasar, 3(2), 220. https://doi.org/10.23887/jisd.v3i2.17775 Ningsih, S. (2014). Realistic Mathematics Education: Model Alternatif Pembelajaran Matematika Sekolah. Jurnal Pendidikan Matematika, 1(2), 73. https://doi.org/10.18592/jpm.v1i2.97 Nisva, L., & Okfrima, R. (2019). Hubungan Antara Regulasi Diri Dengan Palang Merah Indonesia. Jurnal PSYCHE, 12(2), 155–164. Nurina, D. L., & Retnawati, H. (2015). Keefektifan Pembelajaran Menggunakan Pendekatan Problem Posing dan Pendekatan Open-Ended Ditinjau Dari HOTS. PYTHAGORAS: Jurnal Pendidikan Matematika, 10(2), 129. https://doi.org/10.21831/pg.v10i2.9128 Nurlatifah, D., Sudin, A., Maulana, M., & Kontekstual, P. (2017). Perbedaan Pengaruh Antara Pendekatan Realistik Dan Pendekatan Kontekstual Terhadap Pemahaman Matematis Siswa Pada Materi Kesebangunan. Jurnal Pena Ilmiah, 2(1), 961–970. Nurlita, M. (2015). Pengembangan Soal Terbuka (Open-Ended Problem) pada Mata Pelajaran Matematika SMP Kelas VIII. Pythagoras: Jurnal Pendidikan Matematika, 10(1), 38–49. O’Connor, P. A., Morsanyi, K., & McCormack, T. (2018). Young children’s non-numerical ordering ability at the start of formal education longitudinally predicts their symbolic number skills and academic achievement in maths. Developmental Science, 21(5), e12645. https://doi.org/10.1111/desc.12645 Oktaviana, W., Warmansyah, J., & Trimelia Utami, W. (2021). The Effectiveness of Using Big Book Media on Early Reading Skills in 5-6 Years Old. Al-Athfal: Jurnal Pendidikan Anak, 7(2), 157–166. https://doi.org/10.14421/al-athfal.2021.72-06 Östergren, R., & Träff, U. (2013). Early number knowledge and cognitive ability affect early arithmetic ability. Journal of Experimental Child Psychology, 115(3), 405–421. https://doi.org/10.1016/j.jecp.2013.03.007 Pendidikan, M., Kebudayaan, D. A. N., & Indonesia, R. (2014). No Title. Ponitz, C. C., McClelland, M. M., Matthews, J. S., & Morrison, F. J. (2009). A Structured Observation of Behavioral Self-Regulation and Its Contribution to Kindergarten Outcomes. Developmental Psychology, 45(3), 605–619. https://doi.org/10.1037/a0015365 Portilla, X. A., Ballard, P. J., Adler, N. E., Boyce, W. T., & Obradović, J. (2014). An integrative view of school functioning: Transactions between self-regulation, school engagement, and teacher-child relationship quality. Child Development,85(5), 1915–1931. https://doi.org/10.1111/cdev.12259 Prasetya, I., Ulima, E. T., Jayanti, I. D., Pangestu, S. G., Anggraeni, R., & Arfiah, S. (2019). Kegiatan Bimbingan Belajar dalam Meningkatkan Minat Belajar Siswa di Kelurahan Bolong Karanganyar. Buletin KKN Pendidikan, 1(1). https://doi.org/10.23917/bkkndik.v1i1.9286 Purnomo, Y. W., Kowiyah, K., Alyani, F., & Assiti, S. S. (2014). Assessing Number Sense Performance of Indonesian Elementary School Students. International Education Studies, 7(8). https://doi.org/10.5539/ies.v7n8p74 Putra, A. P. (2014). Aji Permana Putra, Eksperimen Pendekatan Pembelajaran... I, 1–10. Qistia, N., Kurnia, R., & Novianti, R. (2019). Hubungan Regulasi Diri dengan Kemandirian Anak Usia Dini. Aulad : Journal on Early Childhood, 2(3), 61–72. https://doi.org/10.31004/aulad.v2i3.35 Rahma, A., & Haviz, M. (2022). Implementation of Cooperative Learning Model with Make A Match Type on Students Learning Outcomes in Elementary School. Journal of Islamic Education Students (JIES), 2(2), 58. https://doi.org/10.31958/jies.v2i2.5593 Rahmawati, F. (2013). Pengaruh Pendekatan Pendidikan Realistik Matematika dalam Meningkatkan Kemampuan Komunikasi Matematis Siswa Sekolah Dasar. Prosiding SEMIRATA 2013, 1(1), 225–238. Rakhman, A., & Alam, S. K. (2022). Metode Bermain Kooperatif Dalam Meningkatkan Antusias Belajar Anak Usia Dini Pada Masa Covid-19. Abdimas Siliwangi, 5(1). https://doi.org/http://dx.doi.org/10.22460/as.v5i1.6880 Riley, D., Juan, robert R. S., Klinkner, J., & Ramminger, A. (2008). Social and Emotional Development. redleaf press. Rismaratri, D., & Nuryadi. (2017). Pengaruh Model Pembelajaran Quantum Dengan Pendekatan Realistic Mathematic Education ( RME ) Terhadap Kemampuan Berfikir Kreatif Dan Motivasi Belajar Matematika. Jurnal Edukasi Matematika Dan Sains, 5(2). Rohmalina, R., Aprianti, E., & Lestari, R. H. (2020). Pendekatan Open-Ended dalam Mempengaruhi Kemampuan Mengenal Konsep Bilangan Anak Usia Dini. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(2), 1409–1418. https://doi.org/10.31004/obsesi.v5i2.805 Roliana, E. (2018). Urgensi Pengenalan Konsep Bilangan Pada Anak Usia Dini. Nasional Pendidikan Dasar, 417–420. Rosdiani, A., & Warmansyah, J. (2021). Perancangan Game Edukasi Berhitung Berbasis Mobile Aplikasi Inventor. Journal of Science and Technology, 1(2), 198–206. Rudyanto, H. E. (2016). Pengembangan Kreativitas Siswa Sekolah Dasar Melalui Pembelajaran Matematika Open-Ended. Premiere Educandum : Jurnal Pendidikan Dasar Dan Pembelajaran, 3(02), 184–192. https://doi.org/10.25273/pe.v3i02.275 Sa’diah, H., Zulhendri, Z., & Fadriati, F. (2022). Development of Learning Videos with Kinemaster-Based Stop Motion Animations on Thematic Learning in Elementary Schools. Journal of Islamic Educational Students (JIES), 2(2), 91. https://doi.org/10.31958/jies.v2i2.5615 Safitri, N. D., Hasanah, U., & Masruroh, F. (2023). The Development of Thematic Board Educational Game Tools to Train The Literacy Skills of Children 5-6 Years Old. Indonesian Journal of Early Childhood Educational Research, 1(2), 75–86. https://doi.org/10.31958/ijecer.v1i2.8156 Salminen, J., Guedes, C., Lerkksnen, M. K., Pakarinen, E., & Cadima. (2021). Teacher – child interaction quality and children s self-regulation in toddler classrooms in Finland and Portugal. December 2020, 1–23. https://doi.org/10.1002/icd.2222 Sarnecka, B. W., & Lee, M. D. (2019). Levels of number knowledge during early childhood. Journal of Experimental Child Psychology, 103(3), 325–337. https://doi.org/10.1016/j.jecp.2009.02.007 Sawyer, A. C. P., Chittleborough, C. R., Mittinty, M. N., Miller-Lewis, L. R., Sawyer, M. G., Sullivan, T., & Lynch, J. W. (2015). Are trajectories of self-regulation abilities from ages 2-3 to 6-7 associated with academic achievement in the early school years? Child: Care, Health and Development, 41(5), 744–754. https://doi.org/10.1111/cch.12208 Setiyawati, Y. (2019). Regulasi Diri Mahasiswa Ditinjau Dari Keikutsertaan Dalam Suatu Organisasi. EMPATI-Jurnal Bimbingan Dan Konseling, 6(1), 245–259. https://doi.org/10.26877/empati.v6i1.4115 Shah, P. E., Weeks, H. M., Richards, B., & Kaciroti, N. (2018). Early childhood curiosity and kindergarten reading and math academic achievement. Pediatric Research, 84(3), 380–386. https://doi.org/10.1038/s41390-018-0039-3 Sriwahyuni, E., Asvio, N., & Nofialdi, N. (2017). Metode Pembelajaran Yang Digunakan Paud (Pendidikan Anak Usia Dini) Permata Bunda. ThufuLA: Jurnal Inovasi Pendidikan Guru Raudhatul Athfal, 4(1), 44. https://doi.org/10.21043/thufula.v4i1.2010 Sudono, A. (2000). Sumber belajar dan alat permainan untuk pendidikan anak usia dini. Grasindo. Sumardi, S., Rahman, T., & Gustini, I. S. (2017). Peningkatan Kemampuan Anak Usia Dini Mengenal Lambang Bilangan Melalui Media Playdough. Jurnal Paud Agapedia, 1(2), 190–202. https://doi.org/10.17509/jpa.v1i2.9359 Supriaji, U., & Soliyah, S. (2021). Upaya Meningkatkan Kemampuan Mengenal Angka Melalui Pendekatan Realistik Matematik Education ( Rme ) Pada Anak Usia 5-6. Jurnal Kridatama Sains Dan Teknologi, 03(01), 1–12. Suseno, P. U., Ismail, Y., & Ismail, S. (2020). Pengembangan Media Pembelajaran Matematika Video Interaktif berbasis Multimedia. Jambura Journal of Mathematics Education, 1(2), 59–74. https://doi.org/10.34312/jmathedu.v1i2.7272 Sutama, I. W., Astuti, W., Pramono, P., Ghofur, M. A., N., D. E., & Sangadah, L. (2021). Pengembangan E-Modul “Bagaimana Merancang dan Melaksanakan Pembelajaran untuk Memicu HOTS Anak Usia Dini melalui Open Ended Play” Berbasis Ncesoft Flip Book Maker. SELING: Jurnal Program Studi PGRA, 7(1), 91–101. http://www.jurnal.stitnualhikmah.ac.id/index.php/seling/article/view/736 Syah, M. (2003). Pendekatan pembelajaran Pendidikan Matematika. Remaja Rosdakarya. Taman, D. I., Cimahi, K. K., Masa, P., & Covid, P. (2020). Jurnal tunas siliwangi. 6(2), 51–62. Utami, N. R., & Warmansyah, J. (2019). Cerita gambar berseri untuk meningkatkan hasil belajar sains di lembaga paud Yogyakarta. Jurnal Tunas Cendekia, 2(2), 89–100. Utami, R. W., Endaryono, B. T., & Djuhartono, T. (2020). Meningkatkan Kemampuan Berpikir Kreatif Matematis Siswa Melalui Pendekatan Open-Ended. Faktor : Jurnal Ilmiah Kependidikan, 7(1). https://doi.org/http://dx.doi.org/10.30998/fjik.v7i1.5328 Utami, S. Y., Muawwanah, U., & Moha, L. (2023). Implementation of Loose Part Media to Increase Creativity in Early Childhood. Indonesian Journal of Early Childhood Educational Research, 1(2), 87–96. https://doi.org/10.31958/ijecer.v1i2.8157 Utoyo, S., & Arifin, I. N. (2017). Model Permainan Kinestetik Untuk Meningkatkan Kemampuan Matematika Awal Pada Anak Usia Dini. JPUD - Jurnal Pendidikan Usia Dini, 11(2), 323–332. https://doi.org/10.21009/JPUD.112.10 Van Herwegen, J., Costa, H. M., Nicholson, B., & Donlan, C. (2018). Improving number abilities in low achieving preschoolers: Symbolic versus non-symbolic training programs. Research in Developmental Disabilities, 77, 1–11. https://doi.org/10.1016/j.ridd.2018.03.011 Warmansyah, J., Sari, R. N., Febriyani, E., & Mardiah, A. (2022). The Effect of Geoquarium Magic Educational Game Tool on The Ability to Recognize Geometry Shapes in Children 4-5 Years Old. The 6th Annual Conference on Islamic Early Childhood Education, 2017, 93–100. Warmansyah, J., Zulhendri, Z., & Amalina, A. (2021). The Effectiveness of Lore Traditional Games Towards The Ability to Recognize The Concept of Numbers on Early Childhood. Ta’dib, 24(2), 79. https://doi.org/10.31958/jt.v24i2.2685 Weller, S. C., Vickers, B., Bernard, H. R., Blackburn, A. M., Borgatti, S., Gravlee, C. C., & Johnson, J. C. (2018). Open-ended interview questions and saturation. 1–18. Widyastuti, N. S., & Pujiastuti, P. (2014). Pengaruh Pendidikan Matematika Realistik Indonesia (PMRI) Terhadap Pemahaman Konsep Dan Berpikir Logis Siswa. Jurnal Prima Edukasia, 2(2), 183. https://doi.org/10.21831/jpe.v2i2.2718 Wijaya, A. (2011). Pendidikan Matematika Realistik Suatu Alternatif Pendekatan Pembelajaran Matematika. Graha Ilmu. Wulandani, C., Afina Putri, M., Indah Pratiwi, R., & Sulong, K. (2022). Implementing Project-Based Steam Instructional Approach in Early Childhood Education in 5.0 Industrial Revolution Era. Indonesian Journal of Early Childhood Educational Research (IJECER), 1(1), 29–37. https://doi.org/10.31958/ijecer.v1i1.5819 Wulandari, N. P. R., Dantes, N., & Antara, P. A. (2020). Pendekatan Pendidikan Matematika Realistik Berbasis Open Ended Terhadap Kemampuan Pemecahan Masalah Matematika Siswa. Jurnal Ilmiah Sekolah Dasar, 4(2), 131. https://doi.org/10.23887/jisd.v4i2.25103 Yanti, D., Widada, W., & Zamzaili. (2018). Kemampuan Pemecahan Masalah Open Ended Peserta Didik Sekolah Negeri Dan Swasta Dalam Pembelajaran Matematika Realistik Berorientasi Etnomatematika Bengkulu. Jurnal Pendidikan Matematika Raflesia, 3(1), 203–209. https://doi.org/https://doi.org/10.31186/jpmr.v3i1.6284 Yilmaz, Z. (2017). Young Children s Number Sense Development : Age-Related Complexity across Cases of Three Children. 9(June), 891–902. Zhou, N., & Yadav, A. (2017). Effects of multimedia story reading and questioning on preschoolers’ vocabulary learning, story comprehension, and reading engagement. Educational Technology Research and Development. https://doi.org/10.1007/s11423-017-9533-2 Zulkarnain, I., & Amalia Sari, N. (2016). Model Penemuan Terbimbing dengan Teknik Mind Mapping untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa SMP. EDU-MAT: Jurnal Pendidikan Matematika, 2(2), 240–249. https://doi.org/10.20527/edumat.v2i2.619